Restless Legs Syndrome among patients receiving antipsychotic and antidepressant drugs. (17th September 2021) - Elrassas, Hanan Hany; Elsayed, Yasser Abdel Razek; Abdeen, Mai SeifElDin; Shady, Mostafa Mohamed; Shalash, Ali; Morsy, Mahmoud
Abstract: Background: Patients with Restless Legs Syndrome (RLS) experience psychological distress and diminished quality of life. Antipsychotics and antidepressants are known to be linked to RLS. Aims: This study aims to investigate the presence of RLS in psychiatric patients who receive antipsychotic and antidepressant drugs and to determine potential risk factors for its occurrence. Methods: Two hundred patients who received antipsychotic and antidepressant drugs for more than 1 month were recruited from two tertiary psychiatric centers in Cairo, Egypt. One hundred apparently healthy volunteers were also included. All patients and controls were screened using the four‐items questionnaire (Arabic version) for RLS. RLS severity was scored according to the validated Arabic version of International Restless Legs Syndrome Study Group rating scale (IRLS). Mimicking conditions were carefully investigated and excluded. Results: Forty‐one percent of the patients who receive antipsychotic and antidepressant drugs were found to have RLS. Family history, past history and smoking are potential risk factors. Trazodone and haloperidol were less associated with RLS. Conclusions: Although limited by its cross‐sectional design, these findings suggest that patients who receive antipsychotic and antidepressant are susceptible to RLS. However, these results need to be replicated on a wider scale.